If you are for market creation, you should be for market destruction! Ethics and the relations between exnovation and innovation for changing direction - Lukas Fuchs; Rafael Ziegler (Journal of Responsible Innovation, 2024)
While innovation and market creation have long received attention for changing the direction of socio-economic development, exnovation and market destruction have received such attention only recently. Rather than assuming innovation and exnovation to be simply two sides of creative destruction processes, we aim to balance the discussion by exploring normative arguments in relation to both innovation and exnovation. We show how instrumental and enabling arguments for changing direction also apply to exnovation. By distinguishing three scenarios – complementation, reversion and reduction – we show that these arguments support genuine creative destruction in the case of a complementary innovation-exnovation relation. In addition, we show that they support an independent focus on exnovation, where the latter relies on reversion to old technologies or on overall reduction of economic activity. We discuss the role of freedom across exnovation processes, and the implication of our analysis for directing societal change without reducing democratic possibilities.